INOVASI IOT UNTUK PENGELOLAAN DAN KEAMANAN RUANG ARSIP: IMPLEMENTASI ESP32 DENGAN SENSOR API DAN SUHU DHT11 - Candra Supriadi; Dwi Setiawan; Lawrence Adi Supriyono; Safira Fegi Nisrina; Mohammad Alfian Mudzakir (CV. Denasya Smart Publisher, 2024)
This study aims to design and develop a prototype IoT-based archive room monitoring system to enhance security and efficiency in archive management at the Village Office of Desa Pingit, Pringsurat District, Temanggung Regency. The system utilizes a UV Flame Detector for fire detection and a DHT11 sensor for monitoring temperature and humidity, with an ESP32 as the main controller connected via Wi-Fi. Integrated with the Telegram app, users can receive real-time notifications and updates on archive room conditions, facilitating remote monitoring. Testing results indicate that the system effectively detects fire presence and accurately provides temperature and humidity updates. This innovation is expected to aid in risk management and archive protection, offering a practical solution for modern archive room management.